Novel SEPSECS Pathogenic Variants Featuring Unusual Phenotype of Complex Movement Disorder With Thin Corpus Callosum: A Case Report. (3rd April 2022) - Nicita, Francesco; Travaglini, Lorena; Bombelli, Francesco; Tosi, Michele; Pro, Stefano; Bertini, Enrico; D'Amico, Adele
Abstract : Objectives: To report a novel association between pathogenic variants in the SEPSECS gene and complex movement disorder with thin corpus callosum (TCC). Methods: Clinical exome sequencing was performed in an adult patient with a genetically unsolved neurodegenerative disorder. The main clinical, neuroimaging, and genetic data were described. Results: The c.865C > T (p.P289S) and c.1297T > C (p.Y433H) missense variants in SEPSECS (NM_016, 955.3) were discovered. Discussion: This case represents a novel form of early-onset pyramidal syndrome with optic nerve hypoplasia, which slowly evolved to extrapyramidal syndrome featuring dystonia-parkinsonism, associated with TCC, caused by SEPSECS pathogenic variants. This form enlarges the group of the so-called pyramidal-extrapyramidal syndromes, as well as complex hereditary spastic paraparesis with TCC.